Reduced sexual functionality of PI‐Wolbachia‐infected females of Tetrastichus coeruleus. Issue 1 (27th August 2014) - Reumer, Barbara M.; van Alphen, Jacques J.M.; Kraaijeveld, Ken
Abstract Wolbachia are endosymbiotic bacteria known to manipulate the reproduction of their hosts by, for example, inducing parthenogenesis. In most cases of Wolbachia‐induced parthenogenesis, the infection is fixed and the entire host population consists of females. In the absence of males and sexual reproduction, genes involved in sexual reproduction are not actively maintained by selection. Accumulation of neutral mutations or selection against maintenance of sexual traits may lead to their loss or deterioration. In addition, females may lose the ability to reproduce sexually due to 'functional virginity mutations' that may spread concomitantly with the Wolbachia infection through a population. The parasitoid wasp Tetrastichus coeruleus (Nees) (Hymenoptera: Eulophidae) forms an ideal model to study the decay of sexual functionality, because it has both Wolbachia‐infected, parthenogenetic populations and uninfected, sexual populations. We compared several components of sexual functionality of arrhenotokous (sexual) and thelytokous (parthenogenetic) T. coeruleus females. First, we tested whether arrhenotokous and thelytokous females were equally attractive and receptive to males. Second, we examined whether mating is costly to females by measuring the life span of mated and virgin females. Last, we studied the morphology of the spermathecae of arrhenotokous and thelytokous females. Mated females had shorter life spans than virgin females, showing that mating carried a fitness cost. Two sexual traits of thelytokous females have degraded compared to arrhenotokous females. Arrhenotokous and thelytokous females were equally attractive to males, but thelytokous females were unreceptive to males. Furthermore, there was a clear difference in spermathecal morphology between arrhenotokous and thelytokous females. Our data do not allow distinction between the various potential causes of such degradation. Although the longevity cost of mating may indicate selection against the maintenance of costly sexual traits, accumulation of neutral mutations, functional virginity mutations, manipulation by Wolbachia, and/or the genetic distance between the two populations may all have contributed to the decay of sexual traits in thelytokous females.